Over-estimating the effects of teacher attributes on school performance in the Chilean education system - Gabriela Toledo Román; Juan Pablo Valenzuela (Estudios de Economía, 2015)
This article investigates the biases involved in estimating the effects of teacher attributes on school's performance. The study was performed for Chilean educational system, where student distribution is differentiated by schools and teachers are not randomly assigned to them. Findings showed that teacher attributes which favored learning appeared more frequently alongside higher socioeconomic status students. When correcting the bias, results showed that the effects of teacher attributes have been overestimated for the vast majority of characteristics. Nonetheless, attributes such as teaching experience, being a woman, having short-term specific professional training, and having a greater curriculum coverage continued to have positive impacts on the performance of 4th grade students.
Keywords: A2; I2; 330; teacher attributes; sorting; school segregation; school performance